MODERN TECHNOLOGIES OF STUDYING FOREIGN LANGUAGE IN THE HIGHER EDUCATIONAL INSTITUTION AS A MEANS OF MOTIVATION OF STUDENTS’ EDUCATIONAL ACTIVITY - Tuxtayeva, Nilufar (Журнал иностранных языков и лингвистики, 2021)
The article is devoted to motivating students to learn a foreign language. The article discussess on pedagogical incentives that increase the stimulation of students when teaching a foreign language. Also, the author highlites difficulties, issues that encountered by teachers in the learning process